SOCIAL MEDIA RESPONSIBILITY: FACTORS INFLUENCING ACADEMIC PERFORMANCE FOR COLLABORATIVE LEARNING AMONG THE COLLEGE LEARNING STUDENTS (Proceedings of the International Conference on Education, 2021)
Social media has modified the manner we tend to live in some ways. It cannot be regarded as a means of spending time because it has introduced the biggest shift since the times of the Industrial Revolution. Indeed, social media has transformed people’s lifestyles and has offered a new pattern of social interaction. This study aims to explore the use of Facebook as a collaborative platform among the college learning students of the UST-IICS. Researching the factors that influence the academic performance of the undergraduates using social media as a venue for collaborative learning came up to a different study. Some may seem very helpful but there are situations that produce a negative outcome. This paper reassesses some descriptions and confers the social software concept. Since this research focused more on the usage of social media, the Honeycomb model for social media was adopted and applied it to the number one social media all over the world, Facebook.This research study is a qualitative case study that can benefit us to recognize the motivations and manners of people, create original insights and ideas, and formulate better research problems and research questions. Based on the study made, many students have positive insights towards the use of social media as a platform for collaborative learning, but there are some who are pessimistic about it. This study has revealed that there is a significant difference between male and female students’ responses concerning the right attitude to use social media sites effectively.
Keywords: academic performance; collabarative learning; facebook; honeycomb model; social media